2001
DOI: 10.1002/1097-0096(200102)29:2<102::aid-jcu1006>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic intrasplenic pseudoaneurysms with delayed rupture: Color Doppler sonographic and CT findings

Abstract: Post‐traumatic intrasplenic pseudoaneurysms are very rare in children. Since pseudoaneurysms may expand a splenic hematoma and cause delayed splenic rupture, early diagnosis and treatment are crucial. In this report, we describe the case of a 12‐year‐old boy with a delayed splenic rupture caused by a splenic hematoma containing 2 pseudoaneurysms. Abdominal sonography showed free intraperitoneal fluid and a mildly enlarged spleen with a large heterogeneous area occupying the upper half of the organ. Two anechoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The apparent healing of SAP in children and the success of NOM is attributed to children's thicker, more fibrous splenic capsule and denser, more elastic parenchyma [1,10]. However, the fear of delayed rupture persists, leading some authors to suggest routine follow-up imaging and embolization [2,[16][17][18]. Others are willing to follow these lesions clinically, given the high success of NOM and the risks of embolization [1,14,19].…”
mentioning
confidence: 99%
“…The apparent healing of SAP in children and the success of NOM is attributed to children's thicker, more fibrous splenic capsule and denser, more elastic parenchyma [1,10]. However, the fear of delayed rupture persists, leading some authors to suggest routine follow-up imaging and embolization [2,[16][17][18]. Others are willing to follow these lesions clinically, given the high success of NOM and the risks of embolization [1,14,19].…”
mentioning
confidence: 99%
“…The follow-up was uneventful patients [83,84,102,108,109,110]. Although partial or total splenectomy has been traditionally performed to manage ruptured pseudoaneurysms in children [89,91,105], embolization has been recently described only in a few cases [90,100].…”
Section: Techniques and Resultsmentioning
confidence: 99%
“…Delayed presentation or diagnosis is due to, respectively, progressive clot lysis at the site of arterial wall injury or to a technical failure in term of timing of contrast bolus injection on CT scan [84]. Although bolus-enhanced CT scan with prompt imaging after iodine injection is highly sensitive to detect intrasplenic vascular malformation [91,100,101,102], it may fail to demonstrate small areas of abnormal enhancement, only identifiable using high-resolution ultrasound. Magnetic resonance imaging could also be effective for the diagnosis of intrasplenic pseudoaneurysm by demonstrating a flow void within the pseudoaneurysm [101,102].…”
Section: Pseudoaneurysmmentioning
confidence: 99%
“…It can be observed that pseudoaneurysm is even bigger than the aorta. only 13 well reported cases [2][3][4][5][6][7][8][9][10][11][12][13] of this complication in the recent English literature searching in Medline (http://www.ncbi.nlm.nih.gov/entrez/query.fcgi) (Table 1 shows 12 cases; Owens [13] reported the last case, not included because the pseudoaneurysm has already ruptured).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been many publications regarding the treatment of this entity either by embolization [1,2] or conservatively [3,4]; both approaches may avoid the need for surgery and splenectomy. However, not all cases are amenable to such solution.…”
Section: Introductionmentioning
confidence: 99%